Anarchy and Archaeology - Flexner, James L.; Gonzalez-Tennant, Edward (Journal of Contemporary Archaeology, 2019)
Anarchist theory is having a ‘moment’ in the social sciences. A growing number of scholars draw on anarchist thought to conceptualize human history and offer solutions grounded in direct democracy for a range of modern ills, including racism, sexism, and structural violence. As scholars wake to the realization that universities have become instruments for the advancement of capital, and as contemporary politics continues to embrace ethnonationalism, neoliberalism, and patriarchy, engagements with anarchist thought and practice have emerged in the academy and more broadly. What does this mean for contemporary archaeology? Here, we raise questions relating to three potential threads: the archaeology of anarchists; the use of anarchism to inform archaeological theory and practice; and the use of archaeological knowledge to inform contemporary anarchisms.